The development of a user-friendly support programme for adolescents living with perinatally acquired human immunodeficiency virus in the Vhembe District of Limpopo Province, South Africa - Mabasa, Rirhandzu Austice (My University, 2022)
There has a significant rise in the number of HIV-infected adolescents who were missed as children and are diagnosed with perinatally acquired HIV as teenagers. In 2013, perinatally acquired HIV was estimated at around 10 000 infections globally, a figure which ballooned to38 000 by 2017. Adolescents living with perinatal HIV experience emotional upheaval as a result of their positive HIV diagnosis, which is exacerbated by real or perceived negative effects on their relationships, career, and family aspirations. They face the same challenges as other adolescents, along with the added complexity of personal decisions relating to their sexual conduct having a direct impact on the global cause to eradicate HIV/AIDS. An extensive body of literature indicates a need for emotional and psychosocial support as existing management focuses mainly on the physical aspects of infection and treatment. Aim of the study The aim of the study was to explore the challenges faced by adolescents living with perinatal HIV infection and to evaluate the designed user-friendly support programme in response to formative findings of the research in selected clinics and community health centres in the Vhembe District of the Limpopo Province in South Africa. Methodology A mixed-methods sequential exploratory design was employed to fulfil the purpose of the study. Data was collected in two phases. In qualitative phase- a total of 21 participants were interviewed using a semi-structured interview guide. The sample was purposefully selected from adolescents living with HIV/AIDS. In quantitative phase a total of 213 people participated in data collection using a questionnaire. Thematic approach was used to analyse qualitative data using Tesch’s eight steps of qualitative data analysis. Quantitative data was analysed using SPSS version 25. Descriptive statistics was used to explain and summarize data. Fischer’s test was done to establish significance of association between alcohol used, condom use and between age and gender. The results The results revealed that adolescents with perinatally acquired HIV face more challenges. They had psychosocial, emotional and economic challenges more than their peers. The current HIV/AIDS management and care has not yet recognised the specific needs these adolescents have related to their care. They have been incorporated into the general adulthood HIV/AIDS making their transition from childhood adolescence difficult. Suggestions for a mentor, and ARV modification were made and a need for a support programme emerged as one of the major themes
Thesis (Ph.D. (Public Health)) -- University of Limpopo, 2022
Keywords: Adolescents; Human-immuno-deficiency Virus; Programme; Support; Perinatal; HIV infections; Prenatal care; HIV-positive persons -- South Africa -- Limpopo; HIV infections -- Treatment; Public Health; Perinatology